Analysis method for polishing slurry for silicon wafers
Patent Information
- Application Number
- JP2022038640
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-11
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-03-11
AI Technical Summary
【0015】 本発明のシリコンウェーハ用の研磨スラリーの分析方法であれば、従来のTRXF分析で生じていたスラリー薄膜の剥離を効果的に防ぐことができる。また、ICP-MS等を用いた従来法に比べて簡便な工程で分析を行うことができる。さらには、感度も十分に高い分析方法である。
Smart Images

Figure 0007635741000015 
Figure 0007635741000016 
Figure 0007635741000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for analyzing metal impurities contained in a polishing slurry used in polishing silicon wafers. [Background technology]
[0002] Polishing slurries (hereinafter simply referred to as "slurries") used in polishing silicon wafers generally contain colloidal silica as the main component, as well as various inorganic and organic substances such as pH adjusters, amines, chelating agents, surfactants, etc. In the processing of silicon wafers, metal contamination can cause deterioration of the characteristics of the wafers, so it is desirable to reduce the level of metal impurities in the slurry.
[0003] Conventional methods for analyzing metal impurities in a slurry include a method in which a mixed acid of hydrofluoric acid (hereinafter, HF) and nitric acid (hereinafter, HNO3) is added to the slurry to dissolve colloidal silica, and the slurry is heated with microwaves, a hot plate, an infrared lamp, or the like to decompose the organic matter contained therein, and then the treated liquid is evaporated to dryness, re-extracted, and analyzed with an inductively coupled plasma mass spectrometer (ICP-MS) (Patent Document 1, Patent Document 2), and a method in which a chelating agent such as ethylenediaminetetraacetic acid (hereinafter, EDTA) is added to the slurry, and then the colloidal silica is separated and removed by centrifugation, and the remaining slurry is analyzed with an ion chromatograph or the like (Patent Document 3). Also, a method for analyzing metal impurities in a solution includes a method in which a specimen is dropped onto a clean silicon wafer, and after drying, the dropped portion is analyzed with a total reflection X-ray fluorescence analyzer (hereinafter, also referred to as TRXF) (Patent Document 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-38843 A [Patent Document 2] JP 2008-20339 A [Patent Document 3] Japanese Patent Application Publication No. 9-260319 [Patent Document 4] JP 2004-109072 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the chemical analysis methods such as those described in Patent Document 1 and Patent Document 2, colloidal silica and organic components in the slurry interfere with the analysis, causing clogging of the sample introduction system and poor analytical accuracy (stability), and these must be completely removed by pretreatment. This makes the process complicated and increases the risk of cross-contamination. In addition, in Patent Document 3, only metals that form chelate complexes can be analyzed, and the influence of contamination caused by chelating agents must be fully considered. In addition, TRXF cannot analyze liquid samples such as slurries, and when the slurry is dropped onto a silicon wafer and the solvent is evaporated to dryness or the like to form a thin film, as in Patent Document 4, the organic components shrink when dried, causing the wafer to peel off from the wafer surface and warp, which is a problem that cannot be analyzed by TRXF.
[0006] The present inventors conducted extensive research and investigated methods for pretreatment of colloidal silica and organic matter in a slurry, and as a result focused on TRXF analysis, which can easily analyze metal impurities in a slurry without using ICP-MS or extraction with a chelate complex. The present invention has been made in consideration of the above-mentioned problems in TRXF analysis, and has an object to provide a method for stably forming and analyzing a thin slurry film without peeling. [Means for solving the problem]
[0007] In order to achieve the above object, the present invention provides a method for analyzing metal impurities in a polishing slurry for silicon wafers, comprising: A step A includes adding hydrofluoric acid to a polishing slurry to be measured to dissolve colloidal silica in the polishing slurry to prepare a slurry solution; A process B of forming a solution film on a silicon wafer with the slurry solution after the process A; A step C of irradiating the solution film formed in the step B with UV light to decompose organic matter in the solution film; a step D of drying the solution film obtained by decomposing the organic matter in the step C on the silicon wafer to form a slurry thin film; A step E of analyzing the metal impurities from the slurry thin film after the step D using a total reflection X-ray fluorescence analyzer; The present invention provides a method for analyzing a polishing slurry for silicon wafers, comprising:
[0008] With this analysis method, the organic matter in the solution film can be decomposed by the UV light irradiation step C, and thus it is possible to prevent the slurry thin film from peeling off due to the organic matter when the solution film is dried to form a slurry thin film in step D. In this way, the slurry thin film can be obtained more stably than with conventional methods, and the subsequent TRXF analysis can be performed reliably. In addition, it is possible to eliminate the need for complicated processes required for chemical analysis using ICP-MS, etc., and analysis is possible even if the colloidal silica and organic matter in the slurry are not completely decomposed or removed, and even if extraction using a chelate complex is not performed, making it very simple. High-sensitivity analysis is possible without using ICP-MS, etc.
[0009] In addition, when the UV light is irradiated in the step C, The solution film can be irradiated with UV light having a wavelength of 344 nm to 179 nm for 10 to 15 minutes.
[0010] If the wavelength of the irradiated UV light is within the above range, organic matter can be decomposed more effectively, and commercially available devices capable of irradiating such UV light are easy to obtain. Furthermore, with the above-mentioned irradiation time, peeling of the thin slurry film can be more reliably prevented, and the influence of secondary contamination due to cross-contamination and the like caused by UV light irradiation can be more effectively suppressed.
[0011] In addition, when drying the solution film in the step D, It can be dried by heating at 70° C. to 100° C., or dried under reduced pressure of 150 Torr (19998.3 Pa) or less.
[0012] Drying under such conditions can more effectively prevent the thin slurry film from peeling off and the effects of secondary contamination.
[0013] In addition, when the solution film is formed in the step B, The slurry solution after the step A can be dropped onto the silicon wafer to form the silicon wafer.
[0014] By forming the film by the dropping method in this manner, secondary contamination due to cross-contamination or the like can be more reliably prevented. Effect of the Invention
[0015] The method for analyzing a polishing slurry for silicon wafers of the present invention can effectively prevent the peeling of the slurry thin film that occurs in conventional TRXF analysis. In addition, the analysis can be performed in a simpler process than conventional methods using ICP-MS, etc. Furthermore, the analysis method has a sufficiently high sensitivity. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a flow chart showing the steps of the polishing slurry analysis method of the present invention. [Diagram 2] 1 is a graph showing the time dependence of secondary contamination in a UV light irradiation environment exposure. [Diagram 3] 1 is a graph showing the time dependence of secondary contamination upon exposure to a heated and dry environment. [Figure 4] FIG. 4 is a flow chart showing steps in another embodiment of the polishing slurry analysis method of the present invention. [Diagram 5] 1 is a graph showing the time dependence of secondary contamination upon exposure to a reduced pressure dry environment. [Figure 6]1 is a graph showing the measurement results of the TRXF spectrum of slurry A in Example 1 (UV light irradiation for 10 minutes + drying under reduced pressure of 150 Torr for 10 minutes). [Figure 7] 1 is a graph showing the measurement results of the TRXF spectrum of slurry B in Example 1 (UV light irradiation for 10 minutes + drying under reduced pressure of 150 Torr for 10 minutes). [Figure 8] 1 is a graph showing the measurement results of the TRXF spectrum of slurry C in Example 1 (UV light irradiation for 10 minutes + drying under reduced pressure of 150 Torr for 10 minutes). [Figure 9] 1 is a graph showing the measurement results of the TRXF spectrum of slurry A in Example 2 (UV light irradiation for 10 minutes + heating and drying at 90° C. for 2 minutes). [Figure 10] 1 is a graph showing the measurement results of the TRXF spectrum of slurry B in Example 2 (UV light irradiation for 10 minutes + heating and drying at 90° C. for 2 minutes). [Figure 11] 1 is a graph showing the measurement results of the TRXF spectrum of slurry C in Example 2 (UV light irradiation for 10 minutes + heating and drying at 90° C. for 2 minutes). [Figure 12] 1 is a graph showing a comparison of the results of Examples 1 and 2 and Comparative Example 1 for Slurry A. [Figure 13] 1 is a graph showing a comparison of the results of Examples 1 and 2 and Comparative Example 1 for Slurry B. [Figure 14] 1 is a graph showing a comparison of the results of Examples 1 and 2 and Comparative Example 1 for Slurry C. [Figure 15] FIG. 1 is a flow diagram showing steps of a conventional method for analyzing abrasive slurry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below with reference to the drawings, while explaining the results of the study of a pretreatment method for the analysis of metal impurities and the process by which the present invention was arrived at; however, the present invention is not limited thereto.
[0018] First, a conventional method for analyzing polishing slurry will be described. Figure 15 is a flow diagram of the process. In the method for analyzing slurry shown in Figure 15, HF is added to the slurry to dissolve colloidal silica contained in the slurry (silicon component dissolving process). SiO2, a component of colloidal silica, dissolves in the liquid in the form of H2SiF6 by reaction with HF, and can be volatilized in the form of SiF4 when evaporated. However, when colloidal silica is dissolved in a mixed acid of HF and HNO3, poorly soluble (NH4)2SiF6 is generated when evaporated, and further thermal decomposition treatment at 200 to 400°C is required.
[0019] Next, the slurry solution with the silicon components dissolved therein is dropped onto any desired location on the clean mirror-finished silicon wafer (slurry dropping process). The silicon wafer used here is not particularly limited, but it particularly refers to a mirror-finished silicon wafer that has been subjected to final cleaning in the silicon substrate manufacturing process and has no metal contamination on the wafer surface or inside the substrate, and is preferably a p-type or n-type silicon wafer with a resistivity of 0.1 Ω cm or more.
[0020] Next, the dropped slurry is evaporated and dried by heating to 50° C. to 100° C. using a hot plate, forming a thin film of the slurry on the wafer (evaporation drying process).
[0021] Finally, the dried slurry thin film is measured by TRXF (TRXF analysis process). To perform TRXF measurement, it is desirable for the sample to be in a thin film form and in a stable state without peeling. Table 1 shows the state of the thin slurry film when the evaporation drying temperature was varied between 50°C and 100°C and the drying time was varied between 8.5 and 1.5 minutes for the method in Fig. 15. When the evaporation drying was performed directly without carrying out the organic matter decomposition treatment as in the flow of the present invention described later, the thin slurry film peeled off from the wafer surface under all conditions, making TRXF analysis impossible, and it was found that the organic matter decomposition process is essential.
[0022] [Table 1]
[0023] Next, the method for analyzing a slurry of the present invention will be described. Fig. 1 is a flow diagram of the steps of the method for analyzing a slurry of the present invention. The slurry analysis method of the present invention shown in Fig. 1 comprises step A: silicon component dissolving step, step B: solution film forming step (slurry dropping step), step C: organic matter decomposition step, step D: slurry thin film forming step (evaporation drying step), and step E: TRXF analysis step. The present invention is characterized in that it includes a step of irradiating a solution film made of a slurry solution with UV light (e.g., light with a wavelength of 185 nm) to decompose the organic matter in the solution film (the above-mentioned organic matter decomposition step) between the slurry dropping step and the evaporation drying step in Fig. 1.
[0024] First, steps A and B will be described. In process A, hydrofluoric acid is added to the polishing slurry to be measured to dissolve the colloidal silica in the polishing slurry to form a slurry solution. In process B, a solution film is formed on a silicon wafer using the slurry solution after process A. These steps can be carried out in the same order as the silicon component dissolving step and the slurry dropping step in FIG. 15 described above. In addition, in regard to step A, a mixed acid of HF and HNO3 may be used. However, as described above, a further pyrolysis treatment is required. Taking into consideration the influence of cross-contamination during this heating, it is more preferable to add HF alone. In addition, regarding the step B, an example of forming a solution film on a silicon wafer by dropping a slurry solution will be described here, but the method of forming the solution film itself is not particularly limited. For example, a method such as coating or immersion may be used, and in that case, appropriate measures can be taken to prevent cross-contamination. A method using dropping is preferable because it can effectively prevent the occurrence of cross-contamination.
[0025] Next, we will explain step C. The solution film formed in step B is irradiated with UV light to decompose the organic matter in the solution film. Here we will explain the relationship between light wavelength and energy. The relationship between UV light wavelength and light energy is expressed by the following formula. E=hc / λ E=Energy (J) h = Planck constant 6.626 x 10 -34 (Js) c=speed of light 2.9979×10 8 (m / s) λ=wavelength 185×10 -9 (m) From this formula, for example, the energy at a wavelength of 185 nm is 1.074 × 10 -18 It becomes J. When converted to 1 mole of photons, Avogadro's number Na = 6.022 × 10 23 / mol, which gives us 647KJ / mol.
[0026] In addition, the molecular bonds and bond energy of organic matter are taken into consideration. Among the representative molecular bonds, OO bond (138.9 KJ / mol), CC bond (347.7 KJ / mol), CO bond (351.5 KJ / mol), CH bond (413.4 KJ / mol), O=O bond (490.4 KJ / mol), and C=C bond (607.0 KJ / mol), UV light with a wavelength of 344 nm or less, which is equivalent to the energy that breaks CC bonds, is particularly effective in decomposing organic matter. However, the light irradiated in step C can be any light with this wavelength as long as it is UV light. Also, some commercially available UV light irradiation devices use an excimer laser with a wavelength of 179 nm, but UV light irradiation devices with a wavelength of 185 nm use a low-pressure mercury lamp and are generally easy to obtain, so are preferred. For these reasons, it is particularly preferable to irradiate with UV light having a wavelength of 344 nm to 179 nm.
[0027] In this organic matter decomposition step C, it is important to prevent the slurry thin film from peeling off after the subsequent step D, which is the slurry thin film formation step by drying. Furthermore, it is preferable to suppress secondary contamination during UV light irradiation.
[0028] Therefore, Test 1 was conducted to examine the relationship between UV light irradiation and peeling of the slurry thin film. Slurry was dropped onto a silicon wafer that had been subjected to the final cleaning of the wafer manufacturing process, and the wafer with the dropped slurry was placed in a polytetrafluoroethylene wafer storage container with a UV light source located 30 mm above the top surface of the wafer. After UV light irradiation was performed by varying the UV light irradiation time between 10 and 30 minutes, the wafer was evaporated and dried at 90°C for 2 minutes, and the condition of the slurry film was then confirmed. In addition, Test 2 was also conducted to investigate the relationship between UV light irradiation and secondary contamination. In addition to Test 1 above, silicon wafers that had been subjected to the final cleaning of the wafer manufacturing process were exposed to the same environment as Test 1 for 10 to 30 minutes without dropping slurry, and then impurities on the wafer surface were subjected to TRXF analysis to investigate the effect of secondary contamination during UV light irradiation. The results are shown in Tables 2 and 3, and in Figure 2. The results for when the UV light irradiation time was 0 minutes (no irradiation) are also shown. The amount of secondary contamination in this case is 1.7 x 10 11 atoms / cm 3 If the concentration is within the range, the device will not be adversely affected and there will be no particular problem. In the analysis method of the present invention, the amount of secondary contamination is not particularly limited to the above-mentioned numerical range, but the UV light irradiation conditions and the like can be appropriately set so as to reduce the amount of secondary contamination.
[0029] [Table 2]
[0030] [Table 3]
[0031] As a result, no peeling of the slurry thin film was observed after drying. In contrast to the conventional method in which peeling occurred without UV light irradiation as shown in Table 1 (and Table 2 with 0 minutes of irradiation time) as shown in Figure 15, peeling was prevented when UV light irradiation was performed. On the other hand, in an investigation of the effects of secondary contamination during UV light exposure, the concentration of impurities increased with increasing exposure time, as can be seen in Figure 2. The UV light irradiation time in step C is not particularly limited, but may be, for example, 10 minutes or more as described above, and 30 minutes is sufficient. In addition to the effect of suppressing peeling of the slurry thin film, taking into consideration the influence of secondary contamination due to cross-contamination and the like caused by UV light irradiation, the UV light irradiation time is preferably in the range of 10 to 15 minutes.
[0032] Next, the step D will be described. The solution film obtained by decomposing the organic matter in the step C is dried on the silicon wafer to form a slurry thin film. Here, the case of drying by heating will be described. The heating method is not particularly limited, and an example of the heating method is a heating method in which the silicon wafer is placed on a hot plate. To investigate the preferable conditions for this process, we conducted Test 3 on the relationship between evaporation and drying and peeling of the slurry thin film. Slurry was dropped onto a silicon wafer that had been subjected to the final cleaning of the wafer manufacturing process, and after 10 minutes of UV light irradiation, the slurry was evaporated and dried on a hot plate at temperatures between 50°C and 100°C for times between 8.5 and 1.5 minutes, and the state of the slurry thin film after that was confirmed. In addition, Test 4 was conducted on the relationship between evaporative drying and secondary contamination. Separately from Test 3 above, a silicon wafer that had been subjected to the final cleaning of the wafer manufacturing process was placed above a hot plate without dripping slurry, and the hot plate was heated under the same conditions as in Test 3 above, during which outgassing from the hot plate was allowed to adhere to the silicon wafer. Thereafter, impurities on the wafer surface on the hot plate side were analyzed by TRXF to investigate the effect of secondary contamination during evaporative drying. The results are shown in Tables 4 and 5, and in Figure 3. As shown in Table 4, the higher the temperature, the shorter the drying time, so the shortest drying time was set for each temperature.
[0033] [Table 4]
[0034] [Table 5]
[0035] No peeling of the slurry thin film was observed after drying. As can be seen from FIG. 3, when the temperature is 90°C or higher, i.e., 90°C (2 minutes) to 100°C (1.5 minutes), the impurity concentration is high even for a short time, whereas when the temperature is lower than 90°C, i.e., 80°C (2.5 minutes) to 50°C (8.5 minutes), the impurity concentration increases as the time increases, regardless of the temperature. The evaporation drying temperature in step D is not particularly limited, but can be, for example, in the range of 50°C to 100°C as described above. Taking into consideration the effects of secondary contamination, a range of 60°C to 100°C, and more preferably a range of 70°C to 100°C, is preferred.
[0036] Then, in step E, the thin slurry film after step D is analyzed for metal impurities using a total reflection X-ray fluorescence analyzer. The total reflection X-ray fluorescence analyzer itself can be a commercially available one, such as the TREX630T manufactured by Technos. The analysis procedure using such an apparatus can be carried out in the same manner as in the conventional method. As mentioned above, in the conventional method, the slurry thin film peels off from the silicon wafer after the solution film is dried, but in the present invention, in which the solution film is irradiated with UV light before drying, the slurry thin film can be prevented from peeling off, and therefore, TRXF analysis can be performed more reliably. Moreover, it can be performed in a simpler process than an analysis method using ICP-MS, etc. Also, as mentioned above, it is fully possible to suppress secondary contamination by adjusting the conditions in each process, and it is possible to perform analysis with the same level of precision as the conventional method.
[0037] If the concentration of impurities in the slurry is high, the TRFX spectrum intensity may be too strong, saturating the detector and making it impossible to perform accurate analysis. In this case, HF can be added to dilute the slurry before performing the pretreatment, enabling stable analysis.
[0038] FIG. 4 shows a method for analyzing a slurry according to another embodiment of the present invention. In the slurry analysis method shown in Fig. 4, a drying step of the solution film by reducing pressure is performed as the slurry thin film formation step in step D (evaporative drying (reduced pressure) step) instead of the evaporative drying (heating) step in Fig. 1. For example, this can be performed by placing a wafer having a solution film in a chamber and reducing the pressure inside the chamber. To investigate the preferable conditions for the drying process under reduced pressure, we conducted Test 5 on the relationship between reduced pressure drying and peeling of the slurry thin film. Slurry was dropped onto silicon wafers that had been through the final cleaning of the wafer manufacturing process, and reduced pressure drying was performed with pressure values ranging from 15 Torr to 760 Torr (1999.83 Pa to 101325 Pa) and times ranging from 2.1 minutes to 120 minutes, and the state of the slurry thin film after drying was confirmed. In addition, Test 6 was conducted on the relationship between reduced pressure drying and secondary contamination. In addition to Test 5, silicon wafers that had been subjected to the final cleaning of the wafer manufacturing process were exposed to the same reduced pressure environment as Test 5 without dropping slurry, and impurities on the wafer surface were analyzed by TRXF to investigate the effect of secondary contamination during reduced pressure drying. The results are shown in Tables 6 and 7, and in Figure 5. Under the reduced pressure drying conditions, the time required for drying increases as the pressure increases, so the shortest drying time was set for each pressure value.
[0039] [Table 6]
[0040] [Table 7]
[0041] No peeling of the slurry film was observed at any pressure. Furthermore, as shown in Figure 5, when exposed to atmospheric pressure, the exposure time was long and the effects of secondary contamination due to cross-contamination, etc. were observed, but in a reduced pressure environment of 150 Torr (19,998.3 Pa) or less, the drying time was short at less than 10 minutes, and it is believed that there is no effect of secondary contamination due to cross-contamination, etc. The pressure in the reduced pressure drying in step D is not particularly limited, but can be, for example, less than 760 Torr (101325 Pa), and taking into consideration the influence of secondary contamination, is particularly preferably 150 Torr (19998.3 Pa) or less as described above. Also, for example, it can be 15 Torr (1999.83 Pa) or more as described above. EXAMPLES
[0042] The present invention will be described in more detail below with reference to examples and comparative examples of the present invention, but the present invention is not limited to these. Example 1 Three types of polishing slurries (slurries A, B, and C) manufactured by Nitta DuPont that are used in the silicon wafer polishing process are analyzed by the analysis method of the present invention as shown in Figure 4. The specific steps are shown below. The wafers onto which the polishing slurry was dropped and dried were 200 mm diameter p-type silicon PW wafers with a resistivity of 9-12 Ωcm that had been subjected to the final cleaning in the wafer manufacturing process. 0.2 mL of the polishing slurry, 9 mL of ultrapure water for dilution, and 0.8 mL of ultrapure hydrofluoric acid (Tapapure-AA100 HF 38%) manufactured by Tama Chemicals to dissolve the colloidal silica in the slurry were placed in a clean PFA (perfluoroalkoxyethylene copolymer) bottle, stirred (total dilution 50 times), and allowed to stand. Then, 0.2 mL of this slurry solution is taken out with a micropipette (manufactured by Eppendorf) and dropped near the center of the cleaned wafer. The dropped slurry solution spreads to a size of about 40 mm in diameter (forming a solution film).
[0043] Next, the wafer on which the solution film has been formed is placed in a UV light irradiation box (UV light irradiation distance: 30 mm) incorporating an ultraviolet lamp with a wavelength of 185 nm, and left for 10 minutes to decompose the organic matter in the solution film. Thereafter, the wafer is transferred to a vacuum chamber equipped with a diaphragm pump, and is left for 10 minutes while the pressure is reduced to 150 Torr (19998.3 Pa), and the slurry is evaporated to dryness by the reduced pressure. When dried, a thin slurry film with a diameter of 40 mm was produced, and this area was measured using a total reflection X-ray fluorescence analyzer (TECHNOS TREX630T).
[0044] The TRXF spectra of slurries A, B, and C are shown in Figures 6, 7, and 8, respectively, and the results of impurities (S, Cl, K, Ca, Ti, Cr, Fe, Ni, Cu, Zn, Ce) in each slurry are shown in Table 8. The unit of impurity concentration by TRXF measurement is atoms / cm. 2 Therefore, the total number of atoms of each element contained in the slurry was calculated from the total area spread by the slurry, and the amount of impurities contained in the original slurry was calculated from the volume of the slurry and the dilution rate, and the results are shown in Table 9.
[0045] [Table 8]
[0046] [Table 9]
[0047] Example 2 The analysis is carried out by an analysis method different from that in Example 1 (see FIG. 1). The slurry and wafers used, and the process from decomposition of the silicon component in the slurry to decomposition of the organic matter are the same as those in Example 1, and therefore a description thereof will be omitted. After the organic matter is decomposed, the wafer is transferred to a hot plate installed in a Class 100 environment and left at 90°C for 2 minutes to evaporate and dry the slurry. When dried, a thin slurry film with a diameter of 40 mm was produced, and this area was measured using a total reflection X-ray fluorescence analyzer (TECHNOS TREX630T).
[0048] The TRXF spectra of slurries A, B, and C are shown in Figures 9, 10, and 11, respectively, and the results of impurities (S, Cl, K, Ca, Ti, Cr, Fe, Ni, Cu, Zn, Ce) in each slurry are shown in Table 10. The unit of impurity concentration by TRXF measurement is atoms / cm. 2 Therefore, the total number of atoms of each element contained in the slurry was calculated from the total area spread by the slurry, and the amount of impurities contained in the original slurry was calculated from the volume of the slurry and the dilution rate, and the results are shown in Table 11.
[0049] [Table 10]
[0050] [Table 11]
[0051] Comparative Example 1 The analysis is carried out by the polishing slurry analysis method described in Patent Document 1. First, 1 mL of the same three types of polishing slurries as in Example 1 was placed in a fluororesin (PFA) beaker, and 1.5 mL of high-purity hydrofluoric acid (Tapapure-AA100 HF 38%) manufactured by Tama Chemical and 0.5 mL of ultra-high-purity nitric acid (Tapapure-AA100 HNO3 68%) manufactured by Tama Chemical were added to dissolve the colloidal silica in the polishing slurry. Next, the organic matter in the slurry is decomposed using a four-stage decomposition recipe using a microwave wet ashing device (manufactured by PerkinElmer) with a maximum output of 1000 W and 2450 MHz. Next, 1 mL of the slurry after the organic decomposition was dropped onto a clean silicon PW wafer with a diameter of 200 mm, and evaporated to dryness for 30 minutes at 70° C. Next, the evaporated to dryness wafer was heated on a hot plate at 350° C. for 10 minutes to volatilize the silicon components in the dried residue. Next, the remaining dry residue was mixed with the above HF and ultra-high purity hydrogen peroxide (Tapapure-AA100 H2O2 30%) manufactured by Tama Chemical to prepare a 2 wt% / 2 wt% aqueous solution, and the dry residue was recovered with 1 mL of the 2 wt% / 2 wt% aqueous solution to prepare the recovered liquid. Finally, the recovered liquid was diluted 200 times with ultrapure water and then analyzed for K, Ca, Ti, Cr, Fe, Ni, Cu, Zn, and Ce using an inductively coupled plasma mass spectrometry (ICP-MS) device (ELEMENT2, Thermo Fisher Scientific). The analytical results of the three slurries are shown in Table 12.
[0052] [Table 12]
[0053] The results of Example 1 (Table 9), Example 2 (Table 11), and Comparative Example 1 (Table 12) are summarized by slurry in Figures 12, 13, and 14 (Slurries A, B, and C, respectively). These results show that Examples 1 and 2 and Comparative Example 1 show roughly equivalent values.
[0054] Comparative Example 2 Unlike the analysis methods of Examples 1 and 2, an analysis method is performed without UV light irradiation. First, prepare the same wafer as in Example 1 and three types of polishing slurries. Since the slurry has a high concentration in the original solution, dilute the slurry as in Example 1, and take 0.2 mL of it and drop it near the center of the cleaned wafer. The wafer was then transferred to a hot plate installed in a class 100 environment and left at 90° C. for 2 minutes to evaporate and dry the slurry. As a result, the dried slurry film peeled off and curled, making TRXF analysis impossible (Table 13). Moreover, when reduced-pressure drying at 150 Torr for 10 minutes was performed instead of evaporation drying using a hot plate, the dried slurry film peeled off and warped, making TRXF analysis impossible (Table 14).
[0055] [Table 13]
[0056] [Table 14]
[0057] In Comparative Example 1, if the amount of colloidal silica contained in the slurry is large, it may cause clogging of the sample introduction system during analysis by ICP-MS, and similarly, if the amount of organic matter is large, it may cause contamination of the sample introduction system or burning of the plasma interface, which may seriously affect the performance of the device. For this reason, it was necessary to decompose the organic matter using microwaves or remove the silicon components by evaporating to dryness. Furthermore, in Comparative Example 2, if the organic matter decomposition treatment by UV light irradiation is not performed, the dried slurry thin film peels off and warps, making TRXF analysis impossible.
[0058] In contrast, as shown in Examples 1 and 2, the analysis method of the present invention performs organic matter decomposition treatment by UV light irradiation, making it possible to form a stable dried film of slurry. In addition, since non-contact analysis is performed by TRXF, there is no risk of components in the thin slurry film contaminating the inside of the device, and there is an advantage that it does not require sufficient organic matter decomposition or silicon component removal as in Comparative Example 1.
[0059] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present invention and that provides similar effects is included in the technical scope of the present invention.
Claims
1. A method for analyzing metal impurities in a polishing slurry for silicon wafers, comprising the steps of: A step A includes adding hydrofluoric acid to a polishing slurry to be measured to dissolve colloidal silica in the polishing slurry to prepare a slurry solution; A process B of forming a solution film on a silicon wafer with the slurry solution after the process A; A process C of irradiating the solution film formed in the process B with UV light to decompose organic matter in the solution film; a step D of drying the solution film obtained by decomposing the organic matter in the step C on the silicon wafer to form a slurry thin film; a step E of analyzing the metal impurities from the slurry thin film after the step D using a total reflection X-ray fluorescence analyzer; A method for analyzing a polishing slurry for silicon wafers, comprising:
2. When the UV light is irradiated in the step C, 2. The method for analyzing a polishing slurry for silicon wafers according to claim 1, wherein the solution film is irradiated with UV light having a wavelength of 344 nm to 179 nm for 10 to 15 minutes.
3. When the solution film is dried in the step D, 3. The method for analyzing a polishing slurry for silicon wafers according to claim 1, wherein the slurry is dried by heating at 70° C. to 100° C. or dried under reduced pressure at 150 Torr (19998.3 Pa) or less.
4. When the solution film is formed in the step B, 4. The method for analyzing a polishing slurry for silicon wafers according to claim 1, wherein the slurry solution after the step A is dropped onto the silicon wafer to form the polishing slurry.
Citation Information
Patent Citations
Detecting method of cu concentration in semiconductor substrate
JP1997064133A
Method of quantitatively analyzing heavy metal ions in semiconductor polishing slurry
JP1997260319A
Silicon wafer polishing liquid and polishing method by use thereof
JP2001237203A
Analysis method for metal impurity in solution
JP2004109072A
Polishing composition
JP2005244123A